Gender Inequality in the Usage of ICT Facilities in Academic Libraries: A Case Study of Presbyterian University College Library (PUCL), Ghana - Boateng, Frank Afoakwa; Ameyaw, Samuel (International Journal of Educational Studies, 2019)
The purpose of the study was to find out gender inequality in the use of ICT facilities in the library among male and female students in the Presbyterian University College of Ghana-Asante Akyem Campus-Ghana. It was a case study which adopted the survey approach with questionnaires as the data collection instrument to solicit the opinions of both genders. The findings disclosed that ICT facilities are available in the library and a significant number of both genders have access to the facilities. However, there were slight variations in the use of the facilities in some domain.Poor internet services, as well as inadequate power supply, were identified as significant challenges that impeded the use of ICT facilities in the library; therefore, it is recommended that measures should be put in place to avoid persistent power failure in the library. Lastly, management of the university should acquire bigger broadband to improve the internet service in the library.